ANALYSIS OF STUDENT ERRORS IN SOLVING STORY PROBLEMS MATERIAL SYSTEM OF LINEAR EQUATIONS WITH TWO VARIABLES AT VOCATIONAL SCHOOL 3 BANDA ACEH - Mainidar Mainidar; Nazariah Nazariah; Nailul Authary (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2024)
This research aims to describe the errors made by students in solving the System of Linear Equations in Two Variables (SPLDV) at SMK 3 Banda Aceh. The type of research used is qualitative research, with research subjects consisting of three students who were selected using purposive sampling techniques based on those who made the most mistakes in solving SPLDV form questions. The instruments used were interviews and error test questions in solving mathematics story problems on SPLDV material, in the form of two questions in the form of descriptions. The data obtained was then analyzed through three stages, namely data reduction, data presentation and drawing conclusions. To maintain the validity of the data, triangulation techniques were also carried out. The research results showed that there were several students' errors in solving two-variable linear equation system (SPLDV) problems such as: (1) Conceptual errors, namely students' errors in understanding story problems, in completing mathematical sentences and not creating mathematical models correctly. The causal factor is that students do not understand the questions given. (2) Principle errors, namely students' errors in using mathematical formulas, drawing conclusions, and determining the final answer. The factors that cause errors are because students are mistaken, lack understanding, are not careful and do not understand the characteristics of SPLDV operations. (3) Operational errors, namely errors made by students in using calculation operations, addition, multiplication and division. The factors that cause errors are because students are not careful and do not understand the questions given.